2023
DOI: 10.1186/s12889-023-14981-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of easing COVID-19 lockdown restrictions on traumatic injuries in Riyadh, Saudi Arabia: one-year experience at a major trauma centre

Abstract: Introduction Lockdown restrictions due to the COVID-19 pandemic have reduced the number of injuries recorded. However, little is known about the impact of easing COVID-19 lockdown restrictions on the nature and outcome of injuries. This study aims to compare injury patterns prior to and after the easing of COVID-19 lockdown restrictions in Saudi Arabia. Method Data were collected retrospectively from the Saudi TraumA Registry for the period between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Unsurprisingly, worldwide, the incidence of violence/aggression and self-inflicted injuries increased during the period of isolation, according to the data (9.17 and 3.43% vs. 8.72 and 1.97%) ( 23-43 ), which is in line with other studies highlighting the negative psychological impact of home isolation caused by COVID-19 worldwide, which could have led to an increase in violence-related injuries ( 38 ). The increase globally in accidental or intentional stabbing injuries has also risen (6.57 vs. 5.63%) ( 25 , 27-32 , 35 , 38 , 39 , 41-43 ). Giudici et al ( 42 ) demonstrated a similar trend of penetrating injuries, especially stabbings, that occurred within families during the pandemic (10.4 vs. 5.2%).…”
Section: Injury Mechanisms and Their Impact On Presentationssupporting
confidence: 89%
See 4 more Smart Citations
“…Unsurprisingly, worldwide, the incidence of violence/aggression and self-inflicted injuries increased during the period of isolation, according to the data (9.17 and 3.43% vs. 8.72 and 1.97%) ( 23-43 ), which is in line with other studies highlighting the negative psychological impact of home isolation caused by COVID-19 worldwide, which could have led to an increase in violence-related injuries ( 38 ). The increase globally in accidental or intentional stabbing injuries has also risen (6.57 vs. 5.63%) ( 25 , 27-32 , 35 , 38 , 39 , 41-43 ). Giudici et al ( 42 ) demonstrated a similar trend of penetrating injuries, especially stabbings, that occurred within families during the pandemic (10.4 vs. 5.2%).…”
Section: Injury Mechanisms and Their Impact On Presentationssupporting
confidence: 89%
“…Firstly, in order to define other mechanisms, they may include burns, explosions, animal bites and injuries caused by natural phenomena. The data we found suggested that these manifested a slight decrease (5.28 vs. 5.63%) ( 23 , 24 , 26 , 27 , 30-32 , 35 , 38-41 ). The most frequent injury mechanisms found in the literature were falls, traffic-related injuries, assaults, gunshot wounds and stabbings.…”
Section: Injury Mechanisms and Their Impact On Presentationsmentioning
confidence: 54%
See 3 more Smart Citations